Studies of Reliability of Power Supply of the Enterprise from the Electric Power System and Autonomous Loaded Generators Based on Markov Processes - Basmanov V.G.; Kholmanskikh V.M.; Suntsov K.A. (Problems of the Regional Energetics, 2024)
The purpose of this work is to substantiate the use of probabilistic components of the availabil-ity factor of the power supply system (PSS) of the enterprise consisting of a electric power sys-tem and autonomous loaded generators, to calculate overpayments for electricity. To achieve this purpose, operation of the PSS during the last 5 years was studied. The PSS was considered as a restored system which has spinning reserve. The process of the PSS functioning was repre-sented by a simple non-branching graph with one repair team and described by systems of dif-ferential and algebraic equations. The solution of the latter allowed calculating the probability components of the PSS availability factor. The operating time of the PSS in a calendar year was calculated with a different number of serviceable generators. The method for calculating over-payment for electricity was proposed. The most significant result is the justification of the use of probability components of the PSS availability factor for assessing overpayment for electricity. The significance of the obtained results lies in the fact that the proposed formula for overpay-ment for electricity allows to estimate overpayment, identify main causes and recommend measures to reduce it. The reliability of the results is confirmed by the example of calculating overpayment for electricity for a real enterprise. The newly obtained indicators of generator reli-ability can be used in the analysis of overpayment by other enterprises, which have similar gen-erators.